2022
DOI: 10.3390/photonics9090652
|View full text |Cite
|
Sign up to set email alerts
|

Design of High Peak Power Pulsed Laser Diode Driver

Abstract: This paper attempts to describe a laser diode driver circuit using the depletion mode gallium nitride high electron mobility transistor (D-mode GaN HEMT) to generate nanosecond pulses at a repetition rate up to 10 MHz from the vertical-cavity surface-emitting laser (VCSEL). The feature of this driver circuit is a large instantaneous laser power output designed in the most efficient way. The design specifications include a pulse duration between 10 ns and 100 ns and a peak power up to above 100 W. The pulsed la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…图3给出了脉冲X射线发生器的时域分析 结果 [13,14] , 可知脉冲X射线发生器的时间特性由 [15,16] , 激光脉冲信号的非线性问题源于激光 二极管的阈值电流特性. 光电阴极X射线管光子 到电子再到X射线的过程中存在的延时 .…”
Section: 脉冲X射线发生器时间特性unclassified
“…图3给出了脉冲X射线发生器的时域分析 结果 [13,14] , 可知脉冲X射线发生器的时间特性由 [15,16] , 激光脉冲信号的非线性问题源于激光 二极管的阈值电流特性. 光电阴极X射线管光子 到电子再到X射线的过程中存在的延时 .…”
Section: 脉冲X射线发生器时间特性unclassified
“…Ching-Yao Liu et al demonstrated a high-peak-power pulsed laser diode driver based on advanced GaN HEMT technology [7]. In addition, further pushing VCSEL lasing wavelengths to blue and UV regimes will definitely lead to novel applications for sensing, visible light communication, and data storage.…”
mentioning
confidence: 99%